Cytokine changes after a marathon race - Nieman, D. C.; Henson, D. A.; Smith, L. L.; Utter, A. C.; Vinci, D. M.; Davis, J. M.; Kaminsky, D. E.; Shute, M. (Journal of Applied Physiology, 2001)
The influence of carbohydrate (1 l/h of a 6% carbohydrate beverage), gender, and age on pro- and anti-inflammatory plasma cytokine and hormone changes was studied in 98 runners for 1.5 h after two competitive marathon races. The marathoner runners were randomly assigned to carbohydrate (C, n = 48) and placebo (P, n = 50) groups, with beverages administered during the races in a double-blind fashion using color codes. Plasma glucose was higher and cortisol was lower in the C than in the P group after the race (P < 0.001). For all subjects combined, plasma levels of interleukin (IL)-10, IL-1 receptor antagonist (IL-1ra), IL-6, and IL-8 rose significantly immediately after the race and remained above prerace levels 1.5 h later. The pattern of change in all cytokines did not differ significantly between the 12 women and 86 men in the study and the 23 subjects 50 yr of age and the 75 subjects <50 yr of age. The pattern of change in IL-10, IL-1ra, and IL-8, but not IL-6, differed significantly between the C and the P group, with higher postrace values measured for IL-10 (109% higher) and IL-1ra (212%) in the P group and for IL-8 (42%) in the C group. In conclusion, plasma levels of IL-10, IL-1ra, IL-6, and IL-8 rose strongly in runners after a competitive marathon, and this was not influenced by age or gender. Carbohydrate ingestion, however, had a major effect in attenuating increases in cortisol and two anti-inflammatory cytokines, IL-10 and IL-1ra.